PENINGKATAN HASIL BELAJAR MATEMATIKA OPERASI HITUNG PENJUMLAHAN PENGURANGAN BERSUSUN DENGAN TABEL KELAS II SEKOLAH DASAR - Anisa Dewi Ardani; Puput Try Kurniasari2; Supriyono (LPPM Universitas Cipta Mandiri, 2025)
Addition and subtraction operations are essential topics in mathematics learning that are highly applicable to daily life, as evidenced by students’ learning outcomes. This study aims to improve student learning outcomes in multi-digit addition and subtraction operations at a primary school in Surakarta through the use of simple visual table media. The research is a classroom action research conducted in two cycles, involving 28 second-grade students as subjects. Data were collected using a quantitative descriptive method. The results show that the use of simple table media effectively improved student learning outcomes. The average score increased from 60 in the pre-cycle to 83 in the second cycle, while the percentage of learning mastery rose from 22 percent to 82 percent. This classroom action research concludes that the use of simple structured table media can enhance the learning outcomes of second-grade students at a primary school in Surakarta during the 2024/2025 academic year.